Perbandingan Volatilitas Return Saham, Emas dan Cryptocurrency : Peluang dan Tantangan sebagai Aset Halal: Perbandingan Volatilitas Return Saham, Emas dan Cryptocurrency : Peluang dan Tantangan sebagai Aset Halal - Noven, Sarah Annisa; Cupian (Jurnal Ilmiah Ekonomi Islam, 2025)
Investment in various financial instrumens such as stocks, gold, and cryptocurrency continues to grow in line with changes in global market conditions. One crucial aspect of investment is understanding return volatility, as high volatility can indicate greater risk for investors. The ARCH/GARCH model has become a widely used method in volatility analysis to capture fluctuations in financial asset prices. This study aims to examine whether the ARCH/GARCH model can explain and predict the return volatility of the Jakarta Islamic Index (JII), gold, and Bitcoin. This research employs a mixed-method approach, where the quantitative method applies the ARCH/GARCH model to analyze the volatility of these three investment instrumens, while the qualitative method involves documentation studies to analyze the opportunities and challenges of cryptocurrency as a halal asset. The findings indicate that the ARCH/GARCH model can explain the return volatility patterns of JII and gold. However, Bitcoin was not included in the ARCH/GARCH modeling. JII exhibits the highest volatility compared to the other two instrumens, whereas gold demonstrates characteristics of a safe-haven asset with lower volatility.